Biopsy and histologic findings of the dura mater at the level of the foramen magnum in 121 CKCS with Chiari-like malformation - Holdsworth, Jaclyn P.; Marino, Dominic J.; Loughin, Catherine A.; Miller, Andrew D.; Sackman, Joseph J.; Lesser, Martin L.; O'Donnell, Marissa (Frontiers in Veterinary Science, 2022)
To describe histopathologic features found in dural biopsies of Cavalier King Charles Spaniels (CKCS) with Chiari-like malformation (CM) and identify any associations between age, duration of clinical signs, syrinx location or syringomyelia (SM) and quality of life (QOL). The medical records of 121 consecutive client owned CKCS with CM and SM, confirmed by whole body magnetic resonance imaging (MRI), that underwent foramen magnum decompression (FMD) with cranioplasty and durectomy with biopsy from 2006 to 2016 were retrospectively reviewed. Dural biopsies were submitted to a board-certified veterinary pathologist for histopathologic interpretation. The chi-square test was used to analyze associations between histologic findings and categorical variables. For continuous measures, the Kruskal-Wallis non-parametric test was used to compare distributions across pathology categories. A result was considered statistically significant at the P<0.05 level of significance. The mean age, duration of pre-surgical clinical signs, and pre-operative QOL (1-5 scale) were 44.27 months, 44.78 weeks, and 2.72 respectively. Syringomyelia was found in the cervical region only in thirty-nine of one hundred twenty-one (32.23%) of dogs, in the cervical and thoracic region only in seventeen of one hundred twenty-one (14.05%) of dogs, and in the cervical, thoracic and lumbar region combined in sixty-five of one hundred twenty-one (53.72%) of dogs. Sixty-six of one hundred twenty-one (54.55%) dural biopsy specimens had histopathology changes; fifty-five (45.45%) did not. Forty-three of one hundred twenty-one (35.54%) dural biopsy specimens had osseous metaplasia, sixteen of one hundred twenty-one (13.22%) had evidence of fibrosis, four of one hundred twenty-one (3.31%) had arachnoid hyperplasia, and three of one hundred twenty-one (2.48%) had evidence of mineralization. Most dogs with CM were found to have histopathologic changes in the dura at the time of FMD cranioplasty was performed. These dural changes can be observed in dogs experiencing clinical signs for a time period as short as four weeks prior to presentation. Histopathologic changes were not associated with age, breed, duration of clinical signs, the location of syringomyelia or QOL. The influence of histopathologic changes on long term prognosis in dogs without dural decompression is unknown since all dogs in this study had dural resection.